Preserving Big Data Privacy in Cloud Environments Based on Homomorphic Encryption and Distributed Clustering - Shatha A. Baker (NTU Journal of Engineering and Technology)
Cloud computing has grown in popularity in recent years because to its efficiency, flexibility, scalability, and the services it provides for data storage and processing. Still, big businesses and organizations have severe concerns about protecting privacy and data security while processing these massive volumes of data.